Response of immobilized bacillus subtilis α‐amylase to high pressure treatment - Butz, Peter; Fister, Heike; Losch, S.; Tauscher, Bernhard (Food biotechnology, 1996)
Immobilized enzymes, advantageous for use in bioreactors, are difficult to decontaminate. Inactivation of microorganisms by high hydrostatic pressure could be a gentle decontamination method, provided the immobilized enzyme is stable enough. Loss in activity of α‐amylase from Bacillus subtilis covalently bound to sepharose, after 10-30 minutes of pressure treatment at 300, 450 und 600 MPa at 50 and 70 °C and pH 8, and after 10-30 minutes of heat treatment at 50 and 70 °C and pH 8, was distinctly lower than that of equally treated non‐immobilized B. subtilis α‐amylase with and without sepharose. At 100 MPa reaction was accelerated by 5 %.